B-lactamase remodeling and evolution of collateral resistance in hypermutator Pseudomonas aeruginosa upon long-term antibiotic therapy - Colque, Claudia Antonella (2021)
Bacteria are endowed with a unique ability to adapt to challenging environments. The evolution of bacterial populations during chronic infections involves a large diversity of adaptive mechanisms that cannot always be reproduced upon controlled laboratory conditions. This creates a gap between the phenotypical description and the underlying biochemical processes that drive that phenotype. Herein, we address the complexity of the bacterial adaptive response to antibiotic selective pressures by studying the in-patient evolution of a broad diversity of β-lactam resistant Pseudomonas aeruginosa hypermutator clones. By using mutational and ultra-deep amplicon sequencing analysis, we analyzed multiple generations of a P. aeruginosa hypermutator strain persisting for more than 26 years of chronic infection in the airways of a cystic fibrosis patient. We identify the accumulation of multiple alterations targeting the chromosomally encoded class C β-lactamase (blaPDC), providing structural and functional protein changes that resulted in a continuous enhancement of its catalytic efficiency and high level of cephalosporin resistance. This evolution was linked to the persistent treatment with ceftazidime, which we demonstrate selected for variants with robust catalytic activity against this expanded-spectrum cephalosporin. Surprisingly, ?a gain of function? of collateral resistance towards ceftolozane, a more recently introduced cephalosporin that was not prescribed to this patient, was also observed and the biochemical basis of this cross-resistance phenomenon was elucidated. This work pinpoints the considerable evolutionary potential of hypermutator strains and uncovers the link between the antibiotic prescription history and the in-patient evolution of resistance.